篮球规则 - 中国篮球协会 (北京市 : 北京体育大学出版社, 2019)
"國際籃聯授權，國籃球協會組織專家翻譯審定。本書是2019年新版，是國際、籃球賽以及各類籃球賽裁判員晉升考試的指定用書，也是籃球教練員、運動員以及廣籃球愛好者的參考書。" --
Translation of : Official basketball rules.
With Chinese and English.
Includes bibliographical references (p. 244).
Keywords: Basketball -- Rules